Educação Patrimonial na “Terra do Sol”: ensino de história a partir do patrimônio cultural material do centro histórico de Monte Santo – BA - Silva, Eduardo dos Santos (2024)
The object of study of this research concerns the places of memory and monuments that make up the material cultural heritage existing in the historic center of Monte Santo, a city located in the northeast of Bahia, in the heart of the Bahian hinterland. The general objective of this work is to analyze the heritage of the historic center of the city of Monte Santo-BA and to present a proposal for the teaching of History study with a sequence of three didactic scripts for the study of de History of the Brazilian Republic, having as theme The War of Canudos, in a class of the 3rd grade of high school. The specific objectives are: to discuss the history of Monte Santo; problematize the constitution of the historic center, its places of memory, monuments, silencing and intentionalities, as well as build a didactic script addressing the existing heritage in it in dialogue with the references on the teaching of History. The need for a study of cultural heritage, the potential of heritage education and its use in the teaching of History are based on the author's experience and in the perception that students do not recognize themselves as historical subjects active in their surroundings; in the lack of heritage education and discussion about the history of the city in history classes, which results in the intense process of deterioration of cultural heritage and the lack of identity and sense of belonging. Thus, this research dialogues theoretically with Nora (1998), Rüsen (2010), Choay (2017) and Zarbato (2018), as well as methodologically based on Heritage Education for the elaboration of its product.